Epidemiology, Monitoring and Evaluation 2017
DOI: 10.1136/sextrans-2017-053264.278
|View full text |Cite
|
Sign up to set email alerts
|

P3.41 Prevalence, socio-demographic and sexual behavioural risk factors for hepatitis b virus infection among pregnant women in southwestern nigeria

Abstract: IntroductionIn endemic countries, Hepatitis B virus (HBV) infection occurs mainly during infancy and early childhood, with vertical transmission from an infected mother being a major route of infection. This study aimed at identifying the prevalence and sexual behavioural risk factors for HBV infection among pregnant women in Ibadan, Nigeria.MethodsA cross-sectional study was done at the antenatal clinic of the University College Hospital Ibadan. One hundred and eighty pregnant women were recruited over a six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
6
13
1
4
Order By: Relevance
“…Another key finding from our study is the significant association between blood transfusion and HBV infection as HBV positive pregnant women were 5 times more likely to have had blood transfusion in the past 3 months. This finding is consistent with similar studies conducted in Nigeria [5,11,23,36] and elsewhere [19,34]. One key explanation for this observed association is the fact that pregnant women in developing countries are prone to obstetric complications due to poor health infrastructure, high cost of specialized medical services along with sub-optimal clinical practices and lack of essential skills among health personnel required to effectively manage their conditions [3,26].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Another key finding from our study is the significant association between blood transfusion and HBV infection as HBV positive pregnant women were 5 times more likely to have had blood transfusion in the past 3 months. This finding is consistent with similar studies conducted in Nigeria [5,11,23,36] and elsewhere [19,34]. One key explanation for this observed association is the fact that pregnant women in developing countries are prone to obstetric complications due to poor health infrastructure, high cost of specialized medical services along with sub-optimal clinical practices and lack of essential skills among health personnel required to effectively manage their conditions [3,26].…”
Section: Discussionsupporting
confidence: 90%
“…For instance, the recent and most nationally representative HBV prevalence burden was reported to be 12.2% [26], while the most comprehensive meta-analytical study conducted till date (2000-2013) on HBV burden in Nigeria found an overall pooled estimate of 13.6% national prevalence and a 14.1% burden in pregnant women attending antenatal clinics across the country [27]. A similar study conducted in the region at the University College Hospital Ibadan, found 8.3% frequency of HBV infection in the study population [23].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…All tubes were sealed and briefly centrifuged before amplification in PCR machine. After amplification, electrophoretic separation of PCR products was performed on 1.5% agarose gel stained with ethidium bromide, and visualized by Ultraviolet illumination (15).…”
Section: Methodsmentioning
confidence: 99%